Inter-subject correlation of temporoparietal junction activity is associated with conflict patterns during flexible decision-making. (July 2019) - Tei, Shisei; Kauppi, Jukka-Pekka; Fujino, Junya; Jankowski, Kathryn F.; Kawada, Ryosaku; Murai, Toshiya; Takahashi, Hidehiko
Highlights: Dynamic conflicting experiences linked with moment-to-moment brain activity patterns. Individual differences accounted for a brain activity-experience association. Right temporoparietal junction activity may be related to conflicting subjectivity. Abstract: Although behavioral flexibility and conflict regulation may rely on executive function, the mechanism underlying these relationships remains obscure. We studied whether subjects' conflict ratings were associated with right dorsolateral prefrontal cortex (rDLPFC) and temporoparietal junction (rTPJ) activity during flexible decision-making in a moral dilemma task using inter-subject correlation (ISC)-based approach (i.e., brain-behavior correlation matrices analysis). We observed a statistically significant positive correlation between the ISC matrix of rTPJ and conflict-scores. This implies that similar rTPJ activity patterns across subjects were associated with similar conflict-rating patterns across subjects. Our findings suggest that rTPJ activity may be also related to conflicting experience.